A single switch high step-up DC-DC converter derived from coupled inductor and switched capacitor for a photovoltaic system - Ali Sepahvandi; Behrooz Rezaeealam; Morteza Mikhak-Beyranvand (Scientific Reports)
Abstract This study suggests a single switch high step-up DC-DC Converter derived from coupled inductor and switched capacitor used in Grid-Connected Photovoltaic systems. In the suggested converter, a part of the yield voltage is produced by parallel charging of the capacitors on the side of the secondary winding and their series discharge together with the secondary winding. The other part of the output voltage is obtained by simultaneously charging the boost and buck-boost capacitors and discharging them in series with the input voltage source. Finally, these two parts make the output voltage in series, so that high voltage gain with proper duty cycle is obtained. In addition, boost and buck-boost capacitors absorb leakage inductance energy leading to a reduction of the switch voltage stress. As a result, switching losses are reduced and by choosing a switch with lower RDS(ON), conduction losses are also reduced. Finally, a prototype with an output power of 200 Watts, and a voltage conversion of 24–400 Volts was made to confirm the performance in the laboratory, which has the highest efficiency of 95.89%.